Where did you cry? Crafting Categories, Narratives, and Affect through Exhibit Design - Kratz, Corinne A (Kronos: Southern African Histories, 2020)
This special issue of Kronos fruitfully focuses on fraught issues related to persons who are missing and missed. Examining the processes involved in becoming ‘missing’, and how the categories related to being missing and missed are created, can offer ways to consider how historical knowledge and political meanings are produced and contested, as well as how diverse disciplinary formations and perspectives come together to constitute such knowledge and meanings. The papers attest to the instability, indeterminacy, and power relations that can pervade questions about evidence – numbers, events, memories, images, and a range of categories (what is a funeral? who is a ‘civilian’? who is counted among the dead?) – as narratives and knowledge about the missing are constituted across a range of contexts.Museum exhibits are one such context, providing a powerful resource through which cultural categories are created and popular histories are shaped and narrated.1 In the process, exhibits can spark the affective and evaluative freight of categories, histories, and narratives, provoke questions, and evoke memories and experiences. Exhibition design is essential to these processes and effects, drawing together verbal, visual, audial, material, and spatial media to craft categories, stories, values, and emotional engagement, as well as to mediate visitors’ understandings and experiences.2 In thinking about the practices and issues that swirl around ‘missingness’, exhibition design offers a productive way to examine how the categories, histories, and politics related to missing persons and the ‘unsettled dead’3 are incorporated into, and produced through, exhibits.